2024
DOI: 10.3390/bs14010063
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Personal Protective Behaviors during Large Social Events: The Value of Behavioral Observations

Ashley Gould,
Lesley Lewis,
Lowri Evans
et al.

Abstract: Within the context of reopening society in the summer of 2021, as the UK moved away from ‘lockdowns’, the Government of Wales piloted the return of organized ‘mass gatherings’ of people at a number of test events. The current study reports behavioral observations that were made at two of the test events to inform this process. The researchers were particularly interested in four key factors: how (1) context within a venue, (2) environmental design, (3) staffing and social norms, and (4) time across an event, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…cigarette packaging, but the approach has been criticized as it can generate anxiety and also does not directly promote the desired behavior [51] though see [52]. However, in certain circumstances, such as during immediate decisions in uncertain circumstances, such interventions may serve to bias behavior in a safer direction [12,52]. In contrast, a natural tendency for communicating risk to groups, is to use higher-level abstract construals (such as public communications) [53].…”
Section: Discussionmentioning
confidence: 99%
“…cigarette packaging, but the approach has been criticized as it can generate anxiety and also does not directly promote the desired behavior [51] though see [52]. However, in certain circumstances, such as during immediate decisions in uncertain circumstances, such interventions may serve to bias behavior in a safer direction [12,52]. In contrast, a natural tendency for communicating risk to groups, is to use higher-level abstract construals (such as public communications) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Concrete representations of the negative consequences of behavior have been widely used in attempts to reduce addictive behaviors, e.g., cigarette packaging, but the approach has been criticized as it can generate anxiety and also does not directly promote the desired behavior [ 52 ] though see [ 53 ]. However, in certain circumstances, such as during immediate decisions in uncertain circumstances, such interventions may serve to bias behavior in a safer direction [ 12 , 53 ]. In contrast, a natural tendency for communicating risk to groups is to use higher-level abstract construals (such as public communications) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, social pain due to rejection has been shown to activate similar areas of the brain to physical pain [ 9 , 10 ] and lacking social support has been linked to an increased risk of mortality [ 11 ]. As such, understanding the key drivers of human social behavior in pandemic contexts provides an important key for a successful response and risk mitigation [ 3 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%